Compressive Crush Performance of Square Tubes Filled with Spheres of Closed-Cell Aluminum Foams - Uzun A. (Walter de Gruyter GmbH, 2017)
AbstractThis paper describes the compressive crush behaviour of spheres of closed-cell aluminium foams with different diameters (6, 8 and 10 mm) and square tubes filled with these spheres. The spheres of closed-cell aluminium foams are net spherical shape fabricated via powder metallurgy methods by heating foamable precursor materials in a mould. The square tubes were filled by pouring the spheres of closed-cell aluminium foams freely (without any bonding). The compressive crush performance of square tubes filled with spheres of closed-cell aluminum foams were compared to that of the empty tubes. The results show a significant influence of the spheres of closed-cell aluminium foam on the average crushing load of the square tubes. The energy absorption in the square tube filled with spheres of closed-cell aluminium foam with diameters of 10 mm is higher than in the other square tubes. The spheres of closed-cell aluminium foams led to improvement of the energy absorption capacity of empty tubes.
Keywords: compression behavior; foam-filled tubes; Mining engineering. Metallurgy; Spheres of closed-cell aluminium foam; TN1-997; TA401-492; energy absorption; Materials of engineering and construction. Mechanics of materials